2(3x+1)+3(1-2x)=
3(x^{2}-2x-2)+x(6-3x)=
x*x+x+x:x= (*=ori)
(2\sqrt{2}*x)^{2}:(3x^{2})
Răspunsuri la întrebare
Răspuns de
1
2(3x+1)+3(1-2x)=6x+2+3-6x=0
5=0
nu are solutii
x∈Ф
3(x²-2x-2)+x(6-3x)=
3x²-6x-6+6x-3x²=0
nu are solutii
x∈Ф
x·x+x+x:x=
x²+x+1=0
Δ=1-4=-3
Δ<0
5=0
nu are solutii
x∈Ф
3(x²-2x-2)+x(6-3x)=
3x²-6x-6+6x-3x²=0
nu are solutii
x∈Ф
x·x+x+x:x=
x²+x+1=0
Δ=1-4=-3
Δ<0
Alte întrebări interesante
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă